PENGARUH PROFESIONALISME AUDITOR TERHADAP PENGUNGKAPAN KECURANGAN (Studi Pada Auditor BPK RI Perwakilan Provinsi Sulawesi Tenggara) - Nurmin, Nurmin (JURNAL AKUNTANSI, 2017)
ABSTRACT This research aimed to examine the effect of Profesionalism Auditor toward Fraud Exposure. Primary data in this study was obtained from all auditors perception of BPK RI Southeast Sulawesi Provincial Repsentative. Perception is measured by questionaire and ordinal measurement with 5 point likert scale. The statistical method used to test each hypotesis is linear regression analysis.the total coefficinet of determination (R2) for the Profesionalism Auditor to the Fraud Exposure is 0,842. The value meant that the contribution amount of profesionalism auditor toward fraud exposure is 84,2% and this meaningful enough, while the remaining amount 15,8% was obtained from othe factors contribution. The result of this research show that profesionalism auditor has significant effect on fraud exposure. Keywords: Profesionalism Auditor, Fraud Exposure